Catalyst-free three-component domino reactions for regioselective synthesis of multi-functional fused pyrroles. Issue 29 (22nd July 2015) - Chen, Xue-Bing; Yan, Sheng-Jiao; Su, An; Liu, Wei; Lin, Jun
Abstract: A three-component domino [3+2] cyclization for the synthesis of new multi-functional fused pyrroles has been developed via reaction of heterocyclic ketene aminals (HKAs) 1 with arylglyoxal monohydrates 2 and 1, 3-diphenylpropane-1, 3-dione 3 under catalyst-free conditions in ethanol. In the one-step domino reaction, one C–N bond and two C–C bonds were formed and one C–C bond was cleaved. The established protocol is advantageous in providing excellent regioselectivity and concise one-pot methodology with the use of environmentally friendly solvents and readily available starting materials. Graphical abstract: